Controlled Hypotension for Functional Endoscopic Sinus Surgery: A Comparative study of Dexmedetomidine and Esmolol (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Functional endoscopic sinus surgery (FESS) requires effective control of bleeding for better visibility of the operating field and reduced risk of injury to the optic nerve or the internal carotid artery. Controlled hypotension is a technique used to limit intraoperative blood loss to provide the best possible field for surgery.Objectives: Our study is undertaken to evaluate the efficacy of dexmedetomidine as a hypotensive agent in comparison to esmolol in Functional Endoscopic Sinus Surgery (FESS).Methods: Sixty (60) patients 20 – 50 years of age, ASA I/II scheduled for FESS were randomly assigned to two equal groups of 30 patients each. Patients of group D received dexmedetomidine 1µg/kg over 10 min before induction of anesthesia followed by 0.4 – 0.8 µg/kg/hr infusion during maintenance and group E received esmolol loading dose 1mg/kg was infused over one min followed by 0.4 – 0.8 mg/kg/hr infusion during maintenance to maintain mean arterial blood pressure (MAP) between (55 – 65 mmHg). The surgical field was assessed using Average Category Scale and average blood loss was calculated. Hemodynamic variables (MAP, HR); intraoperative fentanyl consumption and total recovery from anesthesia (Aldrete’s score ≥9) were recorded. Sedation score was determined at 10, 20, 30, 40 & 60 min after tracheal extubation and time to first analgesic demand was also recorded.Results:In both group D and group E reached the desired MAP (55–65 mmHg) with no inter group difference in MAP or HR. Mean intraoperative fentanyl consumption was significantly lower in group D than group E. Recovery time to achieved Aldrete’s score ≥9 were significantly lower in group E compared with group D.The sedation score were significantly lower in group E compared with group D at 10 minutes, 20 minutes and 30 minutes postoperatively. Time to first analgesic demand was significantly longer in group D.Conclusion: The result of this study showed that both dexmedetomidine and esmolol can be used as agents for controlled hypotension and are effective in providing ideal surgical field during FESS. But dexmedetomidine offers the advantage of inherent analgesic, sedative and anesthetic sparing effect.Bangladesh J Otorhinolaryngol; April 2018; 24(1): 37-49